Oracle PL/SQL programming - Feuerstein, Steven (Sebastopol, CA : O'Reilly & Associates, 1997)
'Oracle8 presents PL/SQL programmers with new challenges by increasing both the possibilities and the complexities of the language. This new edition updates the original book for Oracle8, adding chapters describing the new PL/SQL object features (object types, collections, object views and external procedures). The second edition also contains a much-requested chapter on tuning PL/SQL, as well as expanded discussions of debugging and tracing PL/SQL execution. The accompanying diskette contains the Oracle PL/SQL Programming Companion Utilities Guide, an online tool developed by RevealNet, Inc., with nearly 100 files of source code and documentation prepared by the authors.'--BOOK JACKET.
Book is accompanied by 1 disket entitled'Oracle PL/SQL Programming' bearing the same call number and available at koleski media.
Includes index.
Keywords: Oracle (computer file).; PL/SQL (Computer program language).; Relational databases